Proficiency Testing for ASEAN Member Countries in Analyzing Hydroquinone in Facial Creams, 2011 - Chaivanit, Hansa; Meesri, Junya; Meethong, Sudthida; Anatasinkul, Nawaporn (Journal of Health Science of Thailand, 2017)
Proficiency testing (PT) is an important tool for strengthening the capacity of laboratories. The objective of this study was to assess and compare the performance in the detection and analysis of hydroquinone in facial creams among the ASEAN member countries. There were 10 national cosmetic laboratories from all 10 ASEAN Member Countries (AMC) participated in the study during the period from May to October 2011. In this regard, the Bureau of Cosmetics and Hazardous Substances, Department of Medical Sciences, Ministry of Public Health, Thailand, has provided a known sample for the test. It was found that all 10 AMCs reported the correct results on detection of hydroquinone by thin layer chromatography. Quantitative analysis using high pressure liquid chromatography was performed by 8 AMCs, and the results were all satisfactory. The report of this proficiency testing exercise was distributed to all the AMCs. It was also presented at the ASEAN Cosmetic Committee Meeting in July 2012; and the meeting agreed that the PT should be performed annually.